La responsabilidad civil del estado como consecuencia del enfrentamiento a la crisis de la pandemia COVID-19 en el Perú - Orbe Bardales, Grisel Gianela (2022)
At the end of 2019, a virus was detected that spread very aggressively through China, called "Covid-19", this virus spread through South American countries at the beginning of 2020. As a result of this virus, it affected the way in which we as human beings carry out our daily activities, of which Peru, went through one of the devastating health emergency crises, with increasing numbers of infections, human losses (family members, health personnel, personnel of the Armed Forces, etc.), the system totally affected and with the uncertainty of an economic upheaval almost impossible to restore, the health system totally collapsed. The immobilization and total restriction as a result of the Covid-19 pandemic, as well as unemployment in many entities and institutions, the paralysis and closure of shopping centers, for being a clearly vulnerable population free of contagion and continuous exposure with the spread of this disease. Likewise, it should be noted that in terms of prevention, biosecurity measures, isolation measures and restrictions, added to the dimensions of transmission of the disease, an analysis of the attribution of responsibility is carried out. In these terms, it is necessary to analyze the historical background based on state responsibility.